Penerapan Pendekatan Realistik Mathematics Education (RME) untuk Meningkatkan Pemahaman Konsep Matematis Peserta Didik Kelas IV Sekolah Dasar - Sufianti, Alif Via; Octaviani, Srikandi (Indonesian Research Journal on Education, 2022)
This research is in the background because of the students' understanding in mathematics learningthat causes low student learning outcomes. Based on the problem, one approach that can improvestudents' understanding is Realistic Mathematics Education (RME) approach. The purpose of thisclassroom action research is to know the improvement of students' mathematicsal conceptunderstanding by applying Realistic Mathematics Education (RME) approach. The kind of research is classroom activity includes four stages of research: planning, execution, observationand reflection. This study consists of two cycles. The subjects of this study were fourth gradestudents in one of the elementary schools in the northern metro sub-district which presented 20students. Data processing used is quantitative and descriptive qualitative data analysis. The resultof the research shows improvement of students' mathematicsal concept understanding in eachcycle. This can be seen in the first cycle which is 65.00%, the second cycle 85.00%. Based on theresult of this research, it can be concluded that the application of Realistic Mathematics Education(RME) approach can improve the understanding of mathematicsal concept of fourth grade students of elementary school.